PENGARUH GADGET TERHADAP MOTIVASI BELAJAR ANAK DI EDU PRIVAT BEURAWE - Kandi, Nurlailan; Mardhiah, Ainal; Ismail, Nurjanah; Darmawijaya, Edi (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
This study aims to investigate the effect of gadget use on children's learning motivation at Edu Privat Beurawe. The background of this study states that there is a shift in children's learning interests along with the development of information technology that provides easy access to various learning resources. The use of gadgets among students, although presenting some problems, also offers significant potential in increasing learning motivation. The research method used was a survey with a questionnaire distributed to 17 junior high school students at Edu Privat Beurawe, which explored the frequency of gadget use and its impact on their learning motivation. Data analysis showed that 80% of students used gadgets to study for 2-3 hours per day, and the results indicated a significant positive relationship between gadget use and learning motivation (p < 0.05). Students who actively used gadgets for educational purposes showed higher learning motivation scores with an average of 78 compared to those who used gadgets less who only reached an average of 65. However, around 35% of respondents reported that they were often distracted by non-educational applications, indicating challenges that need to be addressed. This study provides insight into teaching strategies in the digital era that can create a more engaging and effective learning environment for students.